Peran Gaya Mengajar Guru dalam Pembelajaran Aktif Siswa Sekolah Dasar - Sarip Hidayat (STKIP Subang, 2026)
Learning in elementary schools still faces problems of low student participation and motivation, one of which is influenced by teaching styles that are not interactive and do not suit student characteristics. Teaching styles play an important role in creating active and meaningful learning. This study aims to theoretically examine the impact of teachers' teaching styles on the participation and learning motivation of elementary school students. The research method used is a qualitative approach with a literature review. Data were obtained from scientific journal articles and relevant academic sources, which were analyzed using content analysis techniques. The results of the study show that interactive, democratic teaching styles that are appropriate to student characteristics can increase student participation and learning motivation. In addition, the application of adaptive teaching styles creates a conducive, student-centered learning environment. Therefore, the development of appropriate teaching styles is a key factor in improving the quality of learning in elementary schools.